The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
11th AIAA/ISSMO Multidisciplinary Analysis and Optimization Conference 2006
DOI: 10.2514/6.2006-6997
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Global Optimization of Helicopter Rotor Blades for Vibration Reduction in Forward Flight

Abstract: The effectiveness of surrogate based optimization of helicopter rotor blades for vibration reduction using kriging global approximations is investigated. The search for the optimal design is conducted using two methods: (1) the "one-shot" approach in which the surrogate is optimized directly and (2) a method based on the expected improvement function which seeks to find optimal designs while reducing the uncertainty in the surrogate. The results indicate that the more global search based on the expected improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Similar results demonstrating the superiority of the EGO algorithm for optimization in the BVI regime can be found in Ref. 25.…”
Section: Single Objective Function Optimization Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results demonstrating the superiority of the EGO algorithm for optimization in the BVI regime can be found in Ref. 25.…”
Section: Single Objective Function Optimization Resultssupporting
confidence: 77%
“…The EGO algorithm was first applied to the vibration reduction problem in Ref. 25, where it was shown that EGO was superior to "one-shot" optimization for reduction of BVI-induced vibrations. The objectives of this paper are to (1) demonstrate the effectiveness of EGO combined with kriging surrogates for vibration reduction at low advance ratios, where BVI-induced vibrations dominate, as well as high advance ratios where dynamic stall induced vibrations are critical;…”
Section: Introductionmentioning
confidence: 99%
“…This weight scheme was selected for two reasons: (1) so that the EGO algorithm would focus on a more global search initially and then move to a more local search within regions of high probability of improvement, and (2) because these weights were shown to be effective for BVI vibration reduction. 37 The weighted sum approach to multi-objective function optimization was conducted with the following values of W : 0.0, 0.25, 0.50, 0.75 and 1.0. All optimization results are compared to a baseline blade with cross-sectional properties resembling an MBB BO-105 blade.…”
Section: Ivb Passive Reduction Resultsmentioning
confidence: 99%
“…EGO has recently been applied to practical engineering problems by several studies [5][6][7]. EGO was originally built in order to solve unconstrained optimization problems.…”
Section: Introductionmentioning
confidence: 99%